AKTIVITAS ANTIOKSIDAN PADA EKSTRAK JANTUNG PISANG AMBON Musa paradisiaca var sapientum L) DENGAN METODE DPPH - Lia Fikayuniar; Ermi Abriyani; Suamiyati; Aghnia Ahda (Jurnal Buana Farma, 2023)
Banana heart has many benefits for the body, the potential as an antioxidant owned by the ambon banana heart is needed by the body to delay, slow down and prevent the risk caused by free radicals. The purpose of this study was to compare extracts from the heart of Ambonese bananas (Musa paradisiaca var. sapientum L) that can produce the best antioxidant activity. The antioxidant test was carried out using the DPPH (1,1-diphenyl-2-pikrilhydrazil) method, this antioxidant activity test was measured using a UV-Visibe spectrophotometer. The results of the study used three extracts namely ethanol extract, ethyl acetate extract and n-hexane extract of ambon banana heart has activity as an antioxidant. The intensity of antioxidant activity successively from the highest was ethanol extract of 71,129 μg/mL (strong), n-hexane extract of 101,990 μg/mL (medium), ethyl acetate extract of ambon banana heart of 135,311 μg/mL (medium) so that of the three extracts that have the strongest antioxidant activity potential against DPPH free radicals is ambon banana heart ethanol extrac